Optimising Efficiency: Blockchain Implementation In The Financial Audit Process - Kurniasari, Fitria Dita; Akbar, Shofif Sobaruddin; Ernanda, Erni; Ramadani, Nevisa (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Blockchain technology promises the potential to deliver high transparency, security, and efficiency in accounting processes. However, there are many expected benefits of this technology to optimise its application. The purpose of this article is to describe the development and system of blockchain, then identify the potential utilisation of blockchain especially in the field of finance. The research method was conducted through a literature study of relevant articles and sources in the context of blockchain technology and financial auditing. The results of this study indicate that blockchain technology has the potential to be attractive financial process efficiency and fast transaction validation process to reduce the time and cost required so as to help achieve operational performance. The conclusion of this study is that the use of blockchain technology in the financial audit process offers the potential to improve transparency, reliability, and efficiency.